1989
DOI: 10.1038/337449a0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new helical smectic liquid crystal

Abstract: In many biological materials with a hierarchical structure there is an intriguing and unique mechanism responsible for the 'propagation' of order from the molecular to the nano-or micro-scale level. Here we present a much simpler molecular system built of achiral mesogenic dimeric molecules that shows a similar complexity with four levels of structural chirality (i) layer chirality, (ii) helicity of a basic 4-layer repeating unit, (iii) a helix with a pitch of several layers and (iv) mesoscopic helical filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
222
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(234 citation statements)
references
References 15 publications
10
222
0
2
Order By: Relevance
“…Early experiments [10][11][12][13] were crucial in establishing the existence of the defect phase of chiral smectics and confirmed that the morphology of this phase agrees with the predictions of Renn and Lubensky. However, in all these experiments l b and l d were estimated rather than measured.…”
Section: Introductionsupporting
confidence: 56%
“…Early experiments [10][11][12][13] were crucial in establishing the existence of the defect phase of chiral smectics and confirmed that the morphology of this phase agrees with the predictions of Renn and Lubensky. However, in all these experiments l b and l d were estimated rather than measured.…”
Section: Introductionsupporting
confidence: 56%
“…The fact that the helix can be unwound by applied field, also observed in W376, is itself a feature of large electroclinic response. A universal aspect of such large-e electroclinic materials is saturation of (E) at large E (38)(39)(40), typically at Ϸ 30°, indicating that (Ѩ͞Ѩx) 2 or other higher-order terms that act to limit need to be added to the harmonic Landau-deGennes expression for (x) above. Such terms will similarly act to limit ⌬ and would also influence the spatial gradients of Խ(x)Խ and thus the effective correlation length .…”
Section: Discussionmentioning
confidence: 99%
“…The early TGBs (2, 4, 5) exhibited a set of common characteristics, including narrow TGB phase temperature (T) ranges, T R Ϸ 1°C, small angular jumps in layer orientation at the GBs (5), and Grandjean-like textures of the director rotation (TGB) helix (2). However, beginning with the 1993 report of the nitrotolane system having homologs with TGB phase ranges of up to 100°C (6), a distinct class of TGB materials has emerged (6-11) characterized by: (i) large T R values (10°C Ͻ T R Ͻ 100°C); (ii) modulated and͞or undulated Grandjean textures, first described in the ''UTGBC'' phase of the Bangalore S1014͞CE8 mixture (7) and observed in other mixtures (10,11), as well as in neat materials (6,8,9) § § ; (iii) evidence for large angular jumps between blocks, 90°in the case of the UTGBC square lattice (7) and 60°inferred from nitrotolane x-ray data showing 6-fold symmetric block orientation (9); and (iv) electric field-induced unwinding of the TGB helix (6,12).…”
mentioning
confidence: 99%
“…The Twist Grain Boundary phases were first theoretically predicted in 1988 by Renn and Lubensky [64,65] by extending the de Gennes analogy between liquid crystals and superconductors [66] to chiral systems. Already one year later, the TGB phases were observed experimentally [67,68]. In the above mentioned analogy, the Twist Grain Boundary phase is the equivalent of the Abrikosov flux lattice phase of a type II superconductor.…”
Section: Twist Grain Boundary Phasesmentioning
confidence: 99%